Molecular characterization of Duck Plague virus isolated from Bangladesh - Ahamed, Md. Mostakin; Hossain, Muhammad Tofazzal; Rahman, Marzia; Nazir, K. H. M. Nazmul Hussain; Khan, Mohammad Ferdousur Rahman; Parvej, Md. Shafiullah; Ansari, Wahedul Karim; Chiste, Meher Negar Noor-A-Alahi; Amin, Khaled Bin; Hossen, Md. Liakot; Ahmed, Sultan; Rahman, M. Bahanur (Journal of Advanced Veterinary and Animal Research, 2015)
Duck plague (DP) is the most feared duck disease in the world. For isolation, identification, molecular detection and characterization of DP virus (DPV), a total of 94 samples were collected from commercial farms (n=6) and households (n=13) from Rajshahi (n=37), Netrokona (n=35) and Mymensingh (n=22) districts of Bangladesh. The samples were processed and inoculated into 11-13 days old embryonated duck eggs for virus propagation. Virus was identified using agar gel immunodiffusion test (AGIT) and passive hemagglutination (PHA) test, and was confirmed by polymerase chain reaction (PCR) targeting DNA polymerase and gC genes, followed by sequencing. Pathogenicity tests were performed using duck embryos, ducklings and ducks. Among the 94 samples, 17 isolates were confirmed as DPV by PCR amplification of partial DNA polymerase (446-bp) and gC genes (78-bp), respectively. One of the isolates (Anatid herpes 1 BAU DMH) was sequenced and found to be closely related with a Chinese variant of DPV (GenBank: JQ647509.1). Thus, we assume that both Bangladeshi and Chinese isolates of DPV may have a common ancestor. http://dx.doi.org/10.5455/javar.2015.b90